2015
DOI: 10.1242/jeb.114355
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of proteins and solutions: protein adaptation versus cytoprotective micromolecules and their roles in marine organisms

Abstract: Organisms experience a wide range of environmental factors such as temperature, salinity and hydrostatic pressure, which pose challenges to biochemical processes. Studies on adaptations to such factors have largely focused on macromolecules, especially intrinsic adaptations in protein structure and function. However, micromolecular cosolutes can act as cytoprotectants in the cellular milieu to affect biochemical function and they are now recognized as important extrinsic adaptations. These solutes, both inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
116
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 167 publications
0
116
0
Order By: Relevance
“…5. concentrations of 0.6 mol l −1 urea and 0.2 mol l −1 TMAO (Kumemoto et al, 2012). Yancey and Siebenaller (2015) reviewed the roles of TMAO, urea and glycerol, along with several other osmolytes, in cytoprotection. They reported that the counteracting effects of TMAO and urea are related to the differing effects of the two osmolytes on peptide backbone exposure to water.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5. concentrations of 0.6 mol l −1 urea and 0.2 mol l −1 TMAO (Kumemoto et al, 2012). Yancey and Siebenaller (2015) reviewed the roles of TMAO, urea and glycerol, along with several other osmolytes, in cytoprotection. They reported that the counteracting effects of TMAO and urea are related to the differing effects of the two osmolytes on peptide backbone exposure to water.…”
Section: Discussionmentioning
confidence: 99%
“…TMAO acts to stabilize protein structure by forming complexes with water that promote the exclusion of water from the protein backbone (Zou et al, 2002;Canchi and García, 2013). Similar to TMAO, glycerol is predicted to act as a stabilizer of protein structure (Yancey and Siebenaller, 2015). These authors note that while the negative effects of urea in destabilizing protein structure and reducing measures of enzyme function are understood, it is also important to recognize that stabilization is not by definition beneficial (Yancey and Siebenaller, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations